2022
DOI: 10.7759/cureus.22079
|View full text |Cite
|
Sign up to set email alerts
|

Association and Effects of Trauma, Displacement, and Illicit Drug Use on Psychiatric Illnesses in Khyber Pakhtunkhwa, Pakistan

Abstract: Data were accumulated from all patients seen in outpatient clinics from October to December 2020. No inpatients or community samples were included in the research. Verbal consent and approval from the local ethical committee were obtained beforehand. ICD-10 diagnostic criteria were used for all psychiatric diagnoses. ResultsA total of 500 patients were seen with a gender distribution of 51% females and 49% males. Patients aged 18-65 years comprised 79% of this sample; 52% had no formal education. A total of 43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…According to a recent study conducted in Sweden, mental health issues were prevalent among the study's participants, and a relatively large percentage of young people (34-54%) reported issues such as concentration troubles, sleeping dif􀅫iculties, anxiety, and depression, which contributed to substance abuse (Richert et al, 2020). Research conducted in Khyber Pakhtunkhwa also established s strong link between mental health problems and drug abuse (Wazir et al, 2022).…”
Section: Mental Health Issuesmentioning
confidence: 94%
“…According to a recent study conducted in Sweden, mental health issues were prevalent among the study's participants, and a relatively large percentage of young people (34-54%) reported issues such as concentration troubles, sleeping dif􀅫iculties, anxiety, and depression, which contributed to substance abuse (Richert et al, 2020). Research conducted in Khyber Pakhtunkhwa also established s strong link between mental health problems and drug abuse (Wazir et al, 2022).…”
Section: Mental Health Issuesmentioning
confidence: 94%